Digital image correlation (DIC) based stereo matching method for binocular structured light system (BSLS) - Li, Wenjie; Wang, Haijian; Huang, Wenbin; Huang, Yang; Huang, Yuyuan; Wang, Beibei (Oficyna Wydawnicza Politechniki Wrocławskiej, 2025)
With the advantages of non-contact, quick and high accuracy, binocular stereo vision technology is popular in the fields of industrial inspection and measurement. To improve the result of stereo matching, phase consistency constrain based on the fringe projection profilometry (FPP) is performed. The phase unwrapping is generally employed to avoid the phase ambiguity, which is unrobust or time consuming. Aiming at this problem, a digital image correlation (DIC) assisted phase consistency method is proposed to achieve stereo matching with high accuracy, only three fringe patterns and one digital speckle pattern are needed. Two-step strategy is performed to get the homonymy points. The epipolar constraint and DIC algorithm can get the matching with pixel level, and then the wrapping consistency constraint is used to get a sub-pixel matching. To improve the matching accuracy, the Hilbert transform is employed to compensate the phase nonlinear error. As to the regions with low modulation, the disparity refinement algorithm based on neighboring disparity constrain is performed. The experiment results show that the reconstruction accuracy of proposed method is comparative with the multi-step phase shift plus multi-frequency heterodyne method.
Optica Applicata, Vol. 55, 2025, nr 1, s. 77-95
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; Hilbert transformation; digital image correlation; fringe projection profilometry; stereo matching